Spatiotemporal variation in size and abundance of juvenile Chinese mitten crab (Eriocheir sinensis) in Yangtze Estuary - Wu, Yeling; Wang, Sikai; Qin, Ze; Geng, Zhi; Zhao, Feng (Frontiers in Marine Science, 2024)
Introduction Intertidal habitat preferences and spatiotemporal variation in the abundance of juvenile Chinese mitten crab Eriocheir sinensis in Yangtze Estuary are reported. Methods The size and abundance of this crab are reported for mud flat, gravel, root belt, and marsh habitats in this estuary’s lower, middle, and upper reaches from June 2021 (spring) to February 2022 (winter) using quadrat method. Results Juvenile E. sinensis of carapace length (CL) 5.5 ± 2.1 mm (mean ± standard deviation) were collected; no juveniles were found in February 2022. Crab abundance in root belt and gravel habitats usually exceeded that of marsh habitat; no juveniles were found in mud flat habitat. The greatest abundances and smallest individuals were found when megalopa recruited in early spring (June); juvenile abundance decreased sharply afterwards, and crabs were absent from the intertidal during winter. Size and relative growth rate of juvenile crabs were greater in root belt and gravel habitat than in marsh habitat from June to August. Recruitment primarily drove changes in crab abundance and size during June and July, and temperature best correlated with changes in the winter. Many stage I juveniles (CL < 3.1 mm) occurred in the lower estuarine reaches, while stage III and IV juveniles (CL 3.9–6.5 mm) primarily occurred in the middle and upper estuarine reaches. Discussion Although intertidal wetland habitat in Yangtze Estuary is severely degraded and reduced in area, it remains important for recruitment and maintenance of mitten crab populations. An understanding of the habitat requirements of this species will benefit management of this crab resource and the prioritized restoration of intertidal habitat.